2016
DOI: 10.14202/vetworld.2016.1056-1062
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ceruloplasmin, some other acute phase proteins, and biochemical parameters in cows with endometritis

Abstract: Aim:The aim of this study is to determine serum ceruloplasmin levels in cows with endometritis of varying degrees of severity and to establish whether or not there is a correlation between acute phase protein (APP) levels and biochemical parameters.Material and Methods:The study was conducted with 100 Brown Swiss cows (3-8 years of age) on days 28-32 postpartum. Cows were divided into endometritis (mild, moderate, and severe endometriosis) and healthy groups based on ultrasonography, vaginoscopy, and cytologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
(48 reference statements)
2
20
3
Order By: Relevance
“…In research aimed at improving animal health and welfare, ceruloplasmin might be useful (44). Previous studies have reported Cp to be a significant source of data in determining mastitis (3), subclinical mastitis (43), and endometritis (25) in cows. In a prior study on the influence of orchiectomy and dehorning on serum APP levels, sera samples were drawn from seven goats before and after the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…In research aimed at improving animal health and welfare, ceruloplasmin might be useful (44). Previous studies have reported Cp to be a significant source of data in determining mastitis (3), subclinical mastitis (43), and endometritis (25) in cows. In a prior study on the influence of orchiectomy and dehorning on serum APP levels, sera samples were drawn from seven goats before and after the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Haptoglobin has been reported to be present in very low concentrations (<0.1 mg/mL) in healthy animals. But its concentrations increase and remain high in many bacterial, viral, parasitic and inflammatory diseases as long as the stimulus persists [7,[25][26][27][28] . It is a nonspecific marker of tissue damage, and suggested to be used to determine prognosis and severity of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, all the infected sheep fully recovered and no cases of death were observed in the study, supporting to the good prognostic value of haptoglobin. Ceruloplasmin is considered as an indicator of the presence of infection [27,30,31] . It protects the cells against oxidative damage by reducing the effects of oxygen radicals, as well as increasing the phagocytic and antimicrobial efficiency of immune system cells [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased plasma malondialdehyde concentration which is a thiobarbituric acid reactive species, indicate oxidative status . Cows with endometritis had higher ceruloplasmin levels in plasma as positive APP compared with healthy cows (Kaya et al, 2016). During inflammation, copper binding ceruloplasmin mediated formation of reactive oxygen species and may promote oxidative pathology (Shukla et al, 2006).…”
Section: Discussionmentioning
confidence: 99%